IMPLEMENTASI KEBIJAKAN TANGGUNG JAWAB SOSIAL PERUSAHAAN (CORPORATE SOCIAL RESPONSIBILITY) DI KABUPATEN BADUNG PROVINSI BALI (STUDI PADA PT ANGKASA PURA I BANDAR UDARA I GUSTI NGURAH RAI DAN PT AQUA INVESTAMA MAMBAL) - ARTADI SURYA I PUTU HARDI (Jurnal Ilmu Pemerintahan Suara Khatulistiwa, 2023)
Corporate social responsibility have a meaning socially companies have a responsibility to stakeholders and the community as a form of attention in improving the welfare and a positive impact for the environment. However, in its implementation, it still encounters several problems such as the community's not maximally utilizing social responsibility, the lack of maximum resources and transparency. social responsibility activities are not evenly distributed, the communication function of the CSR forum is not yet optimal and the funds collected in the CSR forum are not optimal to support regional development programs. This study attempts to analyze and describe corporate social responsibility in Badung district, the obstacles in the implementation of corporate social responsibility and to determine strategy in solve the problem. Method of the research uses a method of the qualitative descriptive study with inductive approach. The result showed the implementation of corporate social responsibility in Badung district based on Merilee S. Grindle just three indicators have been implemented well enough, namely type of benefit, recources committed, and institution and regime characteristic, while six indicators are not conducted properly. Contributing factors implementation of corporate social responsibility in Badung district the existence of Regional Regulations Regent Badung Number 6 Years 2013 about Corporate Social Responsibility, the positive impact that obtained in the implementation of social responsibility for local governments and companies to avoid from illegal charges and the community accepts with good social responsibility . As for factor inhibitors, is not optimal coordination between local governments and companies, policies that are not conducted by the company, and the community lack of socialization. A strategy that should be applied in the implementation of social responsibility namely regular monitoring the implementation of social responsibility, to evaluate every activity and to increase the community socialization. This research advice to improve the implementation of corporate social responsibility namely concerning the aspect of the implementation of that has not been implemented well,see factors barrier in the implementation corporate social responsibility and consistency the local government to run strategies to solve the problems the implementation of social responsibility . Keyword : Implementation , Corporate Social Responsibility